Inclusion and Neighborhood on a Multivalent q-Symmetric Function with Poisson Distribution Operators - Ebrahim Amini; Shrideh Al-Omari; Dayalal Suthar (Journal of Mathematics)
In this paper, by using Poisson distribution probability, some characteristics of analytic multivalent q-symmetric starlike and q-symmetric convex functions of order η are examined. Then, by utilizing the Poisson distribution and the concept of the q-analogue Salagean integral operator, the p-valent convergence polynomial was introduced. Furthermore, a number of subclasses of analytic symmetric p-valent functions linked to novel polynomials are also deduced. After that, specific coefficient constraints are determined and symmetric δ,q-neighborhoods for p-valent functions are defined. In relation to symmetric δ,q-neighborhoods of q-symmetric p-valent functions formed by Poisson distributions, this paper presents new inclusion results. In addition, a detailed discussion of certain q-symmetric inequalities of analytic functions with negative coefficients is also provided.